Segmentación del mercado crediticio de negocios de consumo de la Financiera Crediscotia en la Provincia de Trujillo, periodo setiembre 2011-agosto 2012 - Rojas Vilcarromero, Neil Martin (2012)
For the development of the research was used as data collection instrument in EXCEL template called SIRA (Information System Agency Network), established by the Financial Crediscotia, to process all your information._x000D_ Technique was used surveys and market specific variables were evaluated our client and also used multivariate statistical techniques such as cluster analysis and discriminant analysis for the collection, processing and analysis._x000D_ Our population The target population consisted of the information was taken from the daily logs of customer database (SIRA) obtained in the assessments in the business area of the Financial Consumer Crediscotia in Trujillo Province, during the period September 2011 - August 2012. This database is N = 1793 cases which pertain to loans and cards activated._x000D_ To assess the credit market segmentation cluster analysis and discriminant analysis models for customer identification._x000D_ It is noted that cluster analysis has been able to form distinct segments in terms of the categories of the study variables of customers who are active your loan or credit card and finally, we present the structure matrix we expresses the correlation between the values of the discriminant function and the variables under study._x000D_ Shows the canonical function coefficients which constitute the model parameters is as follows:_x000D_ D = 3372 + 1212 + 0.02 * FEEDBACK * TERM RELIABILITY + -0297 * 2.84 * evaluated - * QUIEN_OTORGO 0265